Angiopoietin-like protein 4 dysregulation in kidney diseases: a promising biomarker and therapeutic target - Li, Yan; Zhang, Yuxin; Cao, Mengxia; Yuan, Tingting; Ou, Santao (Frontiers in Pharmacology, 2025)
The global burden of renal diseases is increasingly severe, underscoring the need for in-depth exploration of the molecular mechanisms underlying renal disease progression and the development of potential novel biomarkers or therapeutic targets. Angiopoietin-like protein 4 (ANGPTL4) is a multifunctional cytokine involved in the regulation of key biological processes, such as glucose and lipid metabolism, inflammation, vascular permeability, and angiogenesis, all of which play crucial roles in the pathogenesis of kidney diseases. Over the past 2 decades, ANGPTL4 has been regarded as playing a pivotal role in the progression of various kidney diseases, prompting significant interest from the scientific community regarding its potential clinical utility in renal disorders. This review synthesizes the available literature, provides a concise overview of the molecular biological effects of ANGPTL4, and highlights its relationship with multiple renal diseases and recent research advancements. These findings underscore the important gaps that warrant further investigation to develop novel targets for the prediction or treatment of various renal diseases.